Fulfilling Women’s Rights in Jakarta’s Class IIA Prison - Ade Adhari; Anis Widyawati; Indah Aprilia; Amad Sudiro (Faculty of Law Universitas Jenderal Soedirman, 2025)
Correctional institutions function to provide correctional services to inmates who are carrying out criminal sentences. For female prisoners, Indonesia places them in special correctional institutions for women. The Jakarta Class IIA Women's Correctional Institution is one institution formed to guide female WBPs. While in prison, prisoners have rights that must be respected, protected, and fulfilled. This article attempts to establish a national legal policy to guarantee the rights of women inmates in Indonesia and the availability of inmates' rights in Indonesia. This research is yuridis normative. The research results show that at a practical level, there are rights of female prisoners that cannot be accessed, their fulfillment is late, and their fulfillment is a formality to fulfill the provisions of the rules. The various factors that cause non-optimal fulfillment of rights include overcapacity, lack of exceptional standards for female prisoners, inadequate budget, inadequate facilities and infrastructure, weak third-party support, and problems with the quality of human resources for prison officers. The author suggests that the Government fulfill the human rights of inmates by making many changes, such as increasing the budget, collaborating with third parties, and others. Suggestions for the Government to continue to improve the fulfillment of the rights of women prisoners, which is not just a formality but is also optimized, for example, prison capacity, adequate budget, infrastructure, and the quality of prison officer resources.